2007
DOI: 10.1007/s12098-007-0137-4
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous cold abscess

Abstract: A tubercular cold abscess secondary to adjoining bone involvement is a well-known entity. However, a primary cold abscess with no bony involvement in children is very rare. We present such a case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Tuberculosis of the soft tissue is not common except for the occurrence of cold abscesses. The intact skin is a protective barrier to the entry of Mycobacterium tuberculosis 45. Sporadic reports of primary tubercular abscesses in the gluteal region have been presumed to be syringe transmitted either by needles that had been used on more than one patient, or by contamination of the injection site presumably by infected nursing staff coughing over the site 46.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis of the soft tissue is not common except for the occurrence of cold abscesses. The intact skin is a protective barrier to the entry of Mycobacterium tuberculosis 45. Sporadic reports of primary tubercular abscesses in the gluteal region have been presumed to be syringe transmitted either by needles that had been used on more than one patient, or by contamination of the injection site presumably by infected nursing staff coughing over the site 46.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium tuberculosis is a rare but important cause of cold abscess following injections and CB-NAAT is the most sensitive rapid test by which the infection can be diagnosed at the earliest and should be the first test to be done as culture although is the gold standard but it takes time for growth and identification of M. tuberculosis which may delay the treatment. [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the infections are caused by bacterial pathogens which include Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, Pseudomonas spp [1]. Rarely rapid growing nontuberculous mycobacteria (NTM) and M. bovis are also implicated due to contaminated needles or probable use of tap water, the common reservoir of M. chelonae and M. fortuitum [1][2][3][4]. Mycobacterium tuberculosis causing abscess formation at vaccination site is very rare and has been reported by few authors [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…There are sporadic reports of primary soft tissue tuberculosis presenting as gluteal abscess that have been presumed to be syringe transmitted either through used needles or due to coughing by the infected nursing staff over the site of injection [6]. Agrawal et al have reported a case of primary cold abscess where they thought that the spread was hematogenous [2]. There are a few other reports of isolated tubercular involvement of muscles in the literature [7].…”
Section: Discussionmentioning
confidence: 99%
“…Others may present with abscess, fistula, and cutaneous lesion [1]. A tubercular cold abscess secondary to involvement of an adjacent bone or suppuration of lymph nodes is a well-known entity; however, a primary cold abscess is rare [2]. We report one such case which was diagnosed as primary tubercular abscess of the axilla.…”
Section: Introductionmentioning
confidence: 93%